1982
DOI: 10.1161/01.cir.66.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after atrial repair of transposition of the great arteries in early infancy.

Abstract: SUMMARY Fifty-two patients younger than age 100 days who had an intact interventricular septum or a small ventricular septal defect underwent atrial repair of d-transposition of the great arteries (d-TGA). No patient died. To assess long-term results, we evaluated all 36 patients who had been followed for at least 1.5 years (mean 2.7 years) after surgery. The physical findings, chest roentgenograms, ECGs and echocardiograms were reviewed. Catheterization was done 6-60 months (mean 15 months) after surgery in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Both early and late mortality are known to be increased with TGA/ VSD. 4,[13][14][15] Early mortality for this subgroup undergoing atrial switch has been variously reported, but averages around 20%. However, analysis of the mix of simple versus complex cases in this series shows little difference between the 2 groups of atrial switch procedures (Senning 14% complex v Mustard 10%).…”
Section: Discussionmentioning
confidence: 92%
“…Both early and late mortality are known to be increased with TGA/ VSD. 4,[13][14][15] Early mortality for this subgroup undergoing atrial switch has been variously reported, but averages around 20%. However, analysis of the mix of simple versus complex cases in this series shows little difference between the 2 groups of atrial switch procedures (Senning 14% complex v Mustard 10%).…”
Section: Discussionmentioning
confidence: 92%
“…164,166,212 Preoperative cerebral infarctions have been noted in 4% of children with congenital heart defects and are associated with subsequent abnormal neurological development. 105,[213][214][215] Higher bilirubin levels and low birth weight may be associated with a higher rate of neurological complications postoperatively. 216 The abnormal neurology and growth deficits 217 identified in these newborns may either be due to the congenital heart defect or be the result of an earlier factor that has led to both the heart defect and other neurological sequelae, but as yet causal pathways are poorly elucidated.…”
Section: Antenatal and Perinatal Factorsmentioning
confidence: 99%
“…For many years the Mustard operation was the preferred operative repair for transposition of the great arteries [1][2][3]. It was associated with complications such as obstruction of the systemic and/or pulmonary venous pathways, which usually required surgical revision and which carried a risk of morbidity and mortality [4 -6].…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the superior and inferior vena cava after Mustard repair for transposition of the great arteries is a well-documented complication that occurs in 10%-40% of patients [1][2][3]. When both the superior and the inferior systemic venous pathways are obstructed, symptoms are more likely to occur in the form of superior vena cava syndrome, ascites, protein losing enteropathy, and generalized edema [4,5].…”
Section: Introductionmentioning
confidence: 99%